Mixture of glufosinate and atrazine for ryegrass (Lolium multiflorum Lam.) control and its effect on seeds’ quality - André Da Rosa Ulguim; Dirceu Agostinetto; Leandro Vargas; Jessica Dias Gomes da Silva; Theodoro Schneider; Bruno Moncks da Silva (Revista Facultad Nacional de Agronomía Medellín, 2019)
Ryegrass management has been difficult by the occurrence of resistant biotypes to several herbicides with different action mechanisms. Since herbicides mixes and rotations are an important alternative for resistant weed management, the objective of this work was to evaluate the interaction of the dose of the herbicides glufosinate and atrazine on ryegrass control and its seeds’ quality exposed to their association. For this study, three experiments were carried out using factorial design in field, laboratory, and greenhouse conditions. Two factors (A and B) were evaluated in each experiment, where factor A and B represented the doses of glufosinate and atrazine, respectively. Ryegrass control was evaluated in field experiment, while germination percentage and Emergence Speed Index (ESI), were obtained in laboratory and greenhouse analyses, respectively. The data were submitted to variance analysis (P≤0.05) and the significant results were analyzed through response surface graphs. For ryegrass control data, the effect of the interaction was analyzed by the Colby method; glufosinate provides efficient ryegrass control, but its association with atrazine reduces the efficiency, being characterized as an antagonism between molecules. Glufosinate herbicide application, independent of atrazine presence, reduced the ryegrass seeds quality at the post-ﬂowering stage.